Collaboration and authority in the collective action problem - Mehrad, Ahmad (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
Direct reciprocity and contingent collaboration deter opportunistic behavior in social predicaments. However, in large collectives, these mechanisms may lose efficacy as they rely on individuals' influence. Zero-Determinant (ZD) strategies in the collective action problem reshape our understanding of individual influence. Our study introduces a theoretical framework extending these strategies to multiplayer dilemmas, offering insights into lone participants' impact. We delineate intriguing sub-classes of strategies: fair, extortionate (advantageous), and generous (disadvantageous). We explore models showcasing strategic enhancement through alignment with others. The present study elucidates the significance of individual decision-making and collective coordination as essential components contributing to favorable outcomes within expansive group settings.